Designing and Implementing a Zero Harm Falls Prevention Program: A Quality Improvement Study. Issue 3 (4th July 2022) - Wilson, Mary-Agnes; Hacker Teper, Matthew; Sinno, Maya; Kohlberger, Kim; Nuseir, Deema; Chan, Angela; Palomera-Dinglasan, Kristen; Leon, Lauren; Donaldson, Dawn; Taher, Ahmed
Abstract : Background: Inpatient falls with harm have severe implications on patients and the health care system. Purpose: We implemented a zero harm approach to falls prevention, which aimed to reduce falls with injury by 25% within 1 year. Methods: We implemented a multifaceted and multidisciplinary quality improvement falls prevention strategy that included facilitating organization-wide education, adopting the Morse Fall Risk Assessment tool, displaying real-time unit-specific falls rates, and implementing a transparent root-cause analysis process after falls. Our outcome measure was falls with injury per 1000 patient-days. Results: We observed a decrease in the rate of patient falls with injury from 2.03 (baseline period) to 1.12 (1 year later) per 1000 patient-days. We also observed increases in awareness around falls prevention and patient safety incident reporting. Conclusions: Our zero harm approach reduced falls with injury while improving our patient safety culture.